The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.steroids.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil elastase in the tumor microenvironment

Abstract: Myeloid cell production within the bone marrow is accelerated in the setting of cancer, and the numbers of circulating and infiltrating neutrophils and granulocytic myeloid derived suppressor cells (MDSCs) correlate with tumor progression and patient survival. Cancer is therefore able to hijack the normally host-protective immune system and use it to further fuel growth and metastasis. Myeloid cells secrete neutrophil elastase and neutrophil extracellular traps (NETs) in response to cues within the tumor micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
118
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(118 citation statements)
references
References 91 publications
0
118
0
Order By: Relevance
“…Most of the neutrophil-induced pro-tumor effects are associated with the release of NE, CG and PR3, which activate MMPs, and thus mediate tumor invasiveness via their degrading activity against extracellular matrix proteins. In line with this, preclinical studies revealed that genetic deletion or pharmacological inhibition of NE reduces tumor burden and metastatic potential ( Sun and Yang, 2004 ; Ghaedi et al, 2011 ; Lerman and Hammes, 2017 ).…”
Section: The Role Of Aat/neutrophil Interplay In Tumorigenesis and Mementioning
confidence: 73%
“…Most of the neutrophil-induced pro-tumor effects are associated with the release of NE, CG and PR3, which activate MMPs, and thus mediate tumor invasiveness via their degrading activity against extracellular matrix proteins. In line with this, preclinical studies revealed that genetic deletion or pharmacological inhibition of NE reduces tumor burden and metastatic potential ( Sun and Yang, 2004 ; Ghaedi et al, 2011 ; Lerman and Hammes, 2017 ).…”
Section: The Role Of Aat/neutrophil Interplay In Tumorigenesis and Mementioning
confidence: 73%
“… 21 The underlying mechanism(s) may largely depend on the fact that NE has a similar ability as MMPs in causing tissue damage by degrading the structural components of ECM. 22 Moreover, NE can cooperate with MMPs and amplify the effect of ECM degradation. 23 In addition to matrix degradation, NE can also promote peri-bronchial fibrosis by enhancing fibroblast proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Other strategies that have been investigated to target neutrophils in the TME involve inhibition of enzymes and mediators known to induce pro-tumorigenic properties, namely NE ( 182 ), a2 isoform V-ATPase ( 146 ), arachidonate 5-lipoxygenase ( 155 ), IL-23 ( 139 ), and IL-17 ( 183 ). Again, the latter can also promote anti-tumor activities ( 158 ), illustrating that the role of TANs appears to be highly context-dependent, determined by the histological origin and stage of the tumor as well as the therapies applied in the treatment.…”
Section: Neutrophilsmentioning
confidence: 99%